A Way to Investigate the Soundscape of Urban Spaces: A Case Study on The Example of City of Zabrze - Waldemar PASZKOWSKI; Artur KUBOSZEK; Marcin SOBOTA; Marcin DĄBROWSKI; Grzegorz KOPERWAS; Kamil KOWALCZYK; Agata FĄFARA; Agnieszka MAJDA; Sebastian GIEŁŻECKI; Wiktoria PAULUS (Communications of International Proceedings, 2022)
The paper describes the concept of design research on the soundscape in selected places of the urban environment and presents the achieved results of the project related to that. The method of acquiring and processing information about the soundscape and its evaluation has been obtained by means of psychoacoustic tests realized in laboratory conditions. An important element of the carried out research was the development of an application that shares soundscape map information to users using mobile technologies. The application allows identification and assessment of city soundscape.
Keywords: soundscape; acoustic measurements; psychoacoustic test